Сравнительная морфология нервов мышц плечевого сустава некоторых птиц - Сыч, В.Ф. (Вестник зоологии, 1975)
Morphology of extra- and intraorgan nerves of the shoulder joint muscles is shown to be strictly dependent on location and internal structure of the respective muscles. The supracoracoid muscle of birds is found to be a homolog of the superficial pectoral muscle and the great pectoral muscle a homolog of the deep pectoral one of mammals.